Behind A Billion Screens : What Television Tells Us About Modern India - Mehta, Nalin; Introduction by Shankar, Uday (Noida HarperCollins Publishers India, 2015)
What is happening to India's television industry? How is it adapting to the rapid changes in the country? And what does India's television programming tell us about the state of the nation? Television touches almost everyone. It is rapidly expanding and becoming socially ever-more powerful, but is simultaneously facing a crisis of credibility. In Behind a Billion Screens, Nalin Mehta looks closely at how television works in India, how TV channels make their money - or not - and what this means for the cacophony that appears on our screens. Given that television is a strategically vital social gateway for power, he also probes the ownership of television networks - politicians, corporations, real-estate tycoons - and tells us why this matters. Based on extensive research and wide-ranging conversations with industry leaders, channel heads, policy makers and politicians, this is a comprehensive report on the state of the Indian television industry, how it is shapeshifting in response to the ferment of mobiles and social media and its vital role in the wider Indian story. Everybody watches television, everybody has an opinion on it and everybody claims to have solutions, but Mehta brings new research and understanding to illuminate a topic that often raises a lot of heat and smoke but little light.
Include Color Illustrations, Endnotes and Index.
What Television Tells Us About Modern India.
Keywords: Television broadcasting -- Television broadcasting--Social aspects -- India